131 Arteriovenous Malformations of the Posterior Circulation. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Yang, Wuyang; Shang, Hanbing; Caplan, Justin M.; Wang, Joanna; Braileanu, Maria; Hung, Alice; Patel, Varun; Colby, Geoffrey P.; Coon, Alexander Lewis; Tamargo, Rafael J.; Huang, Judy
Abstract: INTRODUCTION: Previous studies have suggested that deep and posterior fossa locations are associated with propensity to hemorrhage and poor functional outcomes in brain arteriovenous malformation (AVM) patients. Few studies have stratified risks within these locations. We therefore sought to clarify hemorrhage risk and functional outcome variations in AVMs that share the angioarchitectural characteristic of posterior circulation arterial supply. METHODS: A retrospective review of all patients with AVMs at Johns Hopkins from 1990 to 2013 was performed. Patients with AVMs involving major supply from the posterior circulation were included in this study (n = 93). AVM locations were categorized into 5 distinct groups (occipital, cerebellum, brainstem, thalamus/basal-ganglia, and others). Functional outcomes were assessed at the last follow-up using modified Rankin Scale (mRS). One-way analysis-of-variances (ANOVA) test was performed for group means of mRS. RESULTS: Forty-eight patients experienced hemorrhage caused by AVM (51.6%). Spetzler-Martin grades were: I (n = 14, 15.1%), II (n = 29, 31.2%), III (n = 26, 28.0%), IV (n = 23, 24.7%), and V (n = 1, 1.1%). Hemorrhagic presentation for the different locations were: occipital (29.0%, n = 9), cerebellum (57.5%, n = 23), thalamus/basal ganglia (63.7%, n = 7), brainstem (100%, n = 8), and others (33.3%, n = 1). Patients were treated with resection (n = 10), radiosurgery (n = 49), embolization (n = 2) or multimodality treatment (n = 24), and 8 patients had observation only. Median follow-up was 29.5 (0-266) months. Three patients died (3.2%) and 5 (5.4%) had recurrent hemorrhages after treatment. Mean mRS at last follow-up for different locations were: occipital (0.8 ± 1.0, n = 31), cerebellum (1.0 ± 1.1, n = 40), thalamus/basal ganglia (1.4 ± 1.8, n = 11), brainstem (2.9 ± 2.6, n = 31), and others (2.0 ± 1.0, n = 3). Difference of group means for mRS were significant ( P < .01). CONCLUSION: Posterior circulation is an effective classification that includes both deep and posterior fossa AVMs. However, clear subgroups are evident with disparate risks of hemorrhage and poor functional outcome. Despite posterior fossa location, cerebellar AVMs are more akin to occipital AVMs, while thalamic/basal ganglia and brainstem AVM locations are comparably associated with higher hemorrhage risk and subsequent worse functional outcome.